Long-Acting β2 Adrenergic Receptor Agonist Ameliorates Imiquimod-Induced Psoriasis-Like Skin Lesion by Regulating Keratinocyte Proliferation and Apoptosis - Xu, Rui; Feng, Shi; Ao, Zhou; Chen, Yingxiang; Su, Congping; Feng, Xiuling; Fu, Qin; Yang, Xiaoyan (Frontiers in Pharmacology, 2022)
Psoriasis is a chronic inflammatory disease that affects approximately 1–5% of the population worldwide. Considering frequent relapse, adverse drug reactions, and large costs of treatment, it is urgent to identify new medications for psoriasis. Keratinocytes play an essential role during psoriasis development, and they express high levels of β2-adrenergic receptor (β2-AR), which increases intracellular cAMP levels when activated. Increased level of cAMP is associated with the inhibition of epidermal cell proliferation. In the present study, we observed the effect of salmeterol, a long-acting β2-AR agonist, on the proliferation and apoptosis of keratinocytes as well as imiquimod-induced psoriasis-like skin lesions in mice. As phosphodiesterase 4 (PDE4) inhibitors increases intracellular cAMP concentration by inhibiting its inactivation, we further explored the synergetic effect of a PDE4 inhibitor and salmeterol on psoriasis-like skin lesions in mice. Our results indicated that salmeterol effectively inhibited the proliferation of HaCaT cells induced by TNF-α and serum, and this effect was accompanied by significantly increased apoptosis and CREB phosphorylation, which were reversed by the PKA inhibitor, H89. Salmeterol ameliorated imiquimod-induced psoriasis-like skin lesions in mice, but salmeterol combined with a PDE4 inhibitor had no synergetic effect in improving skin lesions in mice. Of note, the synergistic effects of anti-proliferation and induction of apoptosis in HaCaT cells appeared by inhibiting ERK signaling. In summary, salmeterol, a long-acting β2-AR agonist, alleviates the severity of psoriasis via inhibiting the proliferation and promoting apoptosis of keratinocytes, partially by activating the cAMP/PKA signaling pathway.